1988
DOI: 10.1111/j.1749-7345.1988.tb00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Induced Ovarian Maturation of Penaeus vannamei by Implantation of Lobster Ganglion

Abstract: Induction of ovarian maturation in Penaeus vannamei, by implantation of ganglion prepared from female lobster, Homarus americanus, with developing ovaries was investigated under tank culture conditions. Four of six females with thoracic ganglion implants were maturing while only two of thirteen females of the control groups with abdominal ganglion or no implant matured. Two ripe stage V were found 18 days after implantation of lobster's thoracic ganglion. This indicates that ovarian maturation of P. vannumei i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 17 publications
(5 reference statements)
5
39
0
Order By: Relevance
“…In the crab U. pugilator, GSF production fluctuates depending on the stage of the annual reproductive cycle (EastmanReks and Fingerman, 1984). Yano and Wyban (Yano and Wyban, 1992) reported that, in a small number of cases, implants of the TG of H. americanus into non-reproductive L. vannamei resulted in the stimulation of ovarian maturation. Injections of aqueous extracts prepared from TG and brain as well as in vitro incubation experiments have shown that vitellogenesis can be stimulated by TG extract (Yano and Wyban, 1992).…”
Section: Role Of Gsfs In Crustacean Reproductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the crab U. pugilator, GSF production fluctuates depending on the stage of the annual reproductive cycle (EastmanReks and Fingerman, 1984). Yano and Wyban (Yano and Wyban, 1992) reported that, in a small number of cases, implants of the TG of H. americanus into non-reproductive L. vannamei resulted in the stimulation of ovarian maturation. Injections of aqueous extracts prepared from TG and brain as well as in vitro incubation experiments have shown that vitellogenesis can be stimulated by TG extract (Yano and Wyban, 1992).…”
Section: Role Of Gsfs In Crustacean Reproductionmentioning
confidence: 99%
“…Yano and Wyban (Yano and Wyban, 1992) reported that, in a small number of cases, implants of the TG of H. americanus into non-reproductive L. vannamei resulted in the stimulation of ovarian maturation. Injections of aqueous extracts prepared from TG and brain as well as in vitro incubation experiments have shown that vitellogenesis can be stimulated by TG extract (Yano and Wyban, 1992). Evidence for GIH seems well established through classical endocrine procedures, but sufficiency studies with the GSF from TG of the central nervous system are lacking, probably because of the difficulty with surgery.…”
Section: Role Of Gsfs In Crustacean Reproductionmentioning
confidence: 99%
“…Similar results were obtained in implantation experiments in the whiteleg shrimp, Li. vannamei (Yano 1988 and Wyban 1992), and crab, Potamon koolooense (Joshi 1989). At this time, the putative VSH could not be fully chemically characterized, but appeared to be a 10 kDa peptide that is inactivated by trypsin (Yano 1998).…”
Section: -1cmentioning
confidence: 99%
“…The well-known reproductive regulatory hormones in crustaceans are gonad-inhibiting hormone/Vitellogenesis inhibiting hormone (GIH/VIH) synthesized and secreted from the X-organ-sinus gland complex located in eyestalk neural tissue [5,6] gonad-stimulating hormone (GSH) synthesized and released from brain and thoracic ganglion [7][8][9][10][11] and a sesquiterpene hormone methyl farnesoate a secretary product of mandibular organ (MO) [12][13][14][15]. In specific MF is a positive regulator for reproduction and is negatively controlled by mandibular organ inhibiting hormone (MOIH) [2,[16][17][18][19] which suppressed the synthesis and release of MF from MO.…”
Section: Introductionmentioning
confidence: 99%